MENELUSURI EMOTIONAL QUOTIENT (EQ) DALAM ISLAM - Baharuddin, Ahmadi (AL-Fikr, 2015)
Discourse on the intelligence trilogy, namely intellectual intelligence (IQ), Emotional Intelligence (EQ) and spiritual intelligence (SQ) today, becoming one of the ways used by a group of people to find success in life. Trilogy intelligence has developed, both in terms of theory and findings that are ready to be held in a practical level. The development is meant here is closely associated with the orientation of thinking that became the basis for these findings. IQ, EQ and SQ when touched by the revelation it will generate tremendous integration. Emotions are always in control, be pious scientists, to directing human has a value of monotheism. IQ, EQ and SQ are part of the repertoire of knowledge that needs to be studied and explored, so it will be born with the knowledge-based and objective understanding especially when coupled with the revelation.